2009
DOI: 10.1166/jnn.2009.c162
|View full text |Cite
|
Sign up to set email alerts
|

The Pulmonary Toxicity of Multi-Wall Carbon Nanotubes in Mice 30 and 60 Days After Inhalation Exposure

Abstract: The pulmonary toxicity, induced by multi-wall carbon nanotubes in mice, was studied after 30-day and 60-day inhalation exposure. The mice were exposed to multi-wall carbon nanotubes aerosol with weighted mean concentration of 32.61 mg/m3, once in very two days, 6 hours in an exposure day. After 30-day and 60-day inhalation exposure, the pulmonary toxicity of multi-wall carbon nanotubes was assessed using biochemical indices in bronchoalveolar lavage fluid and pathological examination. It was found that the aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…While CNT administered via the respiratory tract can cause severe lung damages[36], [37], [38], CNT given intravenously did not affect the long-term survival of the mice[39], [40], [41]. Prior research on the cellular toxicity of CNT mainly focused on the apoptosis or death of target cells following direct CNT exposure in vitro , while the indirect CNT toxicity mediated by the immune cells has not been reported in literature.…”
Section: Discussionmentioning
confidence: 99%
“…While CNT administered via the respiratory tract can cause severe lung damages[36], [37], [38], CNT given intravenously did not affect the long-term survival of the mice[39], [40], [41]. Prior research on the cellular toxicity of CNT mainly focused on the apoptosis or death of target cells following direct CNT exposure in vitro , while the indirect CNT toxicity mediated by the immune cells has not been reported in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that it is possible to generate samples of airborne MWCNT for acute (Mitchell et al 2007(Mitchell et al , 2009Ellinger-Ziegelbauer and Pauluhn 2009) and sub-chronic (Li et al 2009;Ma-Hock et al 2009;Pauluhn 2010) inhalation studies. Samples were generated with a respirable size range at both low dose, between 0.1 and 6 mg/m 3 (Mitchell et al 2007;Ma-Hock et al 2009;Mitchell et al 2009;Pauluhn 2010), and high concentrations, between 11 and 241 mg/m 3 (Ellinger-Ziegelbauer and Pauluhn 2009;Li et al 2009), with aerodynamic diameter of 260-381 nm (Fujitani et al 2009) and 1.9-2.9 mm (Ellinger-Ziegelbauer and Pauluhn 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These inhalation studies have shown MWCNT can, at high doses, cause an increase in inflammatory responses and cytotoxic markers measured in bronchoalveolar lavage (BAL) fluid (Ellinger-Ziegelbauer and Pauluhn, 2009;Li et al 2009), as well as histopathological abnormalities associated with lung and lymph node tissue burden (Ellinger-Ziegelbauer and Pauluhn 2009) and alveolar wall thickening (Li et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles intended for aerosol delivery of drugs need to meet an important criteria of being non immunogenic, otherwise they may elicit inflammatory response through alveolar macrophages. There are several reported cases where different nanoparticles such as carbon nanotubes 8 , silica nanoparticles 9 etc. have found to cause serious pulmonary toxicity by inducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This concern becomes more crucial in the light of several reports, which have proven pulmonary toxicities of inhaled nanoparticles 6 7 . It is also noteworthy that such toxic effects, which include peribronchial inflammation, interstitial fibrosis, oxidative stress etc., are not limited to just inorganic nanoparticles like carbon nanotubes 8 and silica nanoparticles 9 , but have also been found to be associated with certain polymeric and lipid based nanoparticles 10 11 , and have been shown to be a function of nanoparticle parameters such as aspect ratio 12 , degradability 10 , and surface charge 11 13 . Successful clinical translation of this therapeutically beneficial strategy of aerosol drug delivery would therefore require overcoming of the big unmet need of a pulmonary compatible and safe nanocarrier.…”
mentioning
confidence: 99%